INFLUENCES OF GREEN LIGHTING SYSTEM IN SHOPPING CENTER ON CUSTOMER EXPERIENCE: EVIDENCES FROM AEON MALL LONG BIEN IN VIETNAM - HUNG NGUYEN, XUAN; NGUYEN, LE THUY; ANH PHAM, MINH; LINH NGUYEN, THAO (The journal of contemporary issues in business and government, 2022)
The study’s objective is to assess the influence of the green lighting system in the shopping center (AEON Mall Long Bien) on customer experience by testing Structural Equation Model through software SPSS and AMOS. The study was completed based on survey results of 313 observations and combined with interview results obtained from department heads, deputy heads, and departmental staff directly involved in the building management system and the lighting control system. The results show that the green lighting system has a positive influence on customer experience through the following factors of customer experience: Sensorial dimension, Affective dimension, Cognitive dimension, Behavioral dimension, Social dimension.The research’s results imply that rational use of green lighting will bring positive impacts to customer experience, thereby positively influencing the revenue of shopping centers, so shopping centers need to further enhance the green lighting system implementation effectively.